Characteristics of oil palm fruit ash as binder in asphaltic concrete - Bujang, Mastura; Bakie, Nisa ‘Aqila; Bujang, Ummi Humaira; Lee, Siaw Kian; Anak Jusli, Euniza; Wan Azahar, Wan Nur Aifa (UKM Press, 2023)
In order to reduce energy and natural resource consumption during road construction, the sustainability concept needs to be seriously addressed. Oil Palm Fruit Ash (OPFA) is one of the by-products of palm oil production that are typically disposed of in landfills as a result of the growing number of plantations in Malaysia, particularly in Sarawak. Due to the fact that OPFA is known as biomass with pozzolanic qualities (siliceous material), this study was carried out to examine the applicability of OPFA with varying concentrations (0% - 40%) by weight as a modifier in bitumen grade 60/70. Based on the results of the laboratory testing, it was discovered that the modified bitumen provided greater resistance to rutting, temperature, and skid resistance on the bituminous mixture (AC20) compared to the control sample. The 40% OPFA modified samples had the greatest resilient modulus test value, measuring 10992 MPa at 25 °C and 2936 MPa at 40 °C, respectively. In addition, the combination containing 40% OPFA produced the lowest deformation value in the dynamic creep test, which was only 0.20mm, while producing 83.63 skid numbers in the skid resistance test. OPFA can be utilized as a binder modifier to improve the performance of bituminous mixture, which indirectly supports the sustainable development goals (SDGs) concept in road construction, as this study conclusively demonstrated.